Ethnicity, Inc. - Comaroff, John L. 1945- (The University of Chicago Press, 2009)
Exploring the changing relationship between culture and the market, this book addresses the question: Wherein lies the future of ethnicity? It offers an account of the ways in which ethnic populations are remaking themselves in the image of the corporation - while corporations coopt ethnic practices to open up new markets of consumption.